ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN RETAIL PUPUK UREA NONSUBSIDI PT PUPUK ISKANDAR MUDA DI KABUPATEN ACEH UTARA - Zainal Abiddin; Julimursyida Julimursyida; Ichsan Ichsan (J-MIND (Jurnal Manajemen Indonesia), 2020)
This study aims to determine the effect of product excellence and brand trust on customer loyalty through customer satisfaction as an intervening variable. This study uses primary data obtained by distributing questionnaires to 144 respondents, who are the retail customers of non-subsidized urea fertilizer of PT Pupuk Iskandar Muda in the North Aceh Regency. The method used to analyze the data is Structural Equation Modeling (SEM). The results find that brand trust significantly influences customer satisfaction and customer loyalty, but product excellence does not significantly influence customer satisfaction and Retail customer loyalty of non-subsidized urea fertilizer of PT Pupuk Iskandar Muda in North Aceh Regency. Furthermore, customer satisfaction mediates the influence of brand trust on retail customer satisfaction of non-subsidized urea fertilizer of  PT Pupuk Iskandar Muda in the North Aceh Regency. Based on the results of the study, it is expected that the leaders of PT Pupuk Iskandar Muda to increase customer loyalty, it is necessary to pay attention to the efforts for growing and increasing brand trust in customers by creating positive perceptions of costumers about the benefits that can be given by the products/brands so that they are confident in using non-subsidized urea fertilizer of PT Pupuk Iskandar Muda in North Aceh Regency Keywords:             product excellence, brand trust, customer satisfaction and customer loyalty